Does recollection contribute to unitized associative memory? The roles of repetition learning and memory strength - Liu, Xiangshen; Wang, Lingwei; Yang, Jiongjiong (Learning & memory (Cold Spring Harbor, N.Y.), 2025)
The ability to remember the relationship between unrelated events is a powerful cognitive function. When two unrelated stimuli are encoded in a condition of high level of unitization (LOU), the associative memory could be acquired with a strong familiarity contribution. This provides a promising way for brain lesioned patients to obtain a new associative memory. However, recent studies are inconsistent on the extent to which the recollection process is involved in unitized associative memory. To clarify this issue, two groups of participants learned unrelated word pairs once or twice in the high- and low-LOU conditions and were tested at 10 min and 24 h. The recollection and familiarity processes were estimated by dual-process models. Results showed that both recollection and familiarity were stronger for the high- than for the low-LOU condition. However, when memory strength was controlled, recollection was comparable for high- and low-LOU conditions, while familiarity still showed a significant effect of LOU. In addition, the effect of LOU for familiarity increased after repetition learning. The results suggest that the recollection contribution to unitized association is related to memory strength, but the familiarity contribution is stably observed and increases after repetition learning when unrelated word pairs are used. These findings are also significant for memory rehabilitation in aging and brain lesioned patients.